KONSEP JENIS PALEM: SEBUAH PENGANTAR - Rustiami, Himmah (Research Center for Biology-Indonesian Institute of Sciences, 2009)
In recent decade, the needs of clear species concept for constructing monograph became more crucial. Trends on species concept have been more overwhelming nowadays because of the rigorous phylogenetic species concept based on the idea of the smallest unit sexually from a single population or based on the known lineages within taxa in regard with unique characters combination.This paper would like to discuss further how is the palm species concept and their distribution pattern in West Malesia using case study on the Nypa species concept.